The Cochrane Database of Systematic Reviews (Protocol) 2002
DOI: 10.1002/14651858.cd003781
|View full text |Cite
|
Sign up to set email alerts
|

Anticholinergic drugs versus placebo for overactive bladder syndrome in adults

Abstract: The use of anticholinergic drugs by people with overactive bladder syndrome results in statistically significant improvement in symptoms. However, the clinical significance of these differences is uncertain, and the longer-term effects are not known. Dry mouth is a common side effect of therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 63 publications
1
39
0
4
Order By: Relevance
“…4 On the other hand, the efficacy and clinical significance of anticholinergics has been reviewed, 5 challenging the apparent discrepancy between the statistical significance of anticholinergics in trials and the 'modest improvement in quality of life'. 6 Furthermore, the overall discontinuation rate of anticholinergics in randomised, double-blind clinical trials was reported to be 4 to 31 per cent, with discontinuation due to adverse events or side-effects observed to range between 0 and 21 per cent. Newer preparations, eg solifenacin, do not necessarily carry a lower discontinuation rate compared with the old generation, eg tolterodine.…”
Section: Declaration Of Interestsmentioning
confidence: 99%
“…4 On the other hand, the efficacy and clinical significance of anticholinergics has been reviewed, 5 challenging the apparent discrepancy between the statistical significance of anticholinergics in trials and the 'modest improvement in quality of life'. 6 Furthermore, the overall discontinuation rate of anticholinergics in randomised, double-blind clinical trials was reported to be 4 to 31 per cent, with discontinuation due to adverse events or side-effects observed to range between 0 and 21 per cent. Newer preparations, eg solifenacin, do not necessarily carry a lower discontinuation rate compared with the old generation, eg tolterodine.…”
Section: Declaration Of Interestsmentioning
confidence: 99%
“…Oxybutynin is usually prescribed at the dose of 5 mg twice a day with the possibility to increase it up to 10 mg 3 times a day [11] . The use of slow-release systems of oxybutynin could improve patient compliance when compared to the immediate-release formulation [12] , although some data are controversial [13] .…”
Section: Anticholinergic Agentsmentioning
confidence: 99%
“…Tolterodine is a relatively new antimuscarinic drug characterized by a greater selectivity for the lower urinary tract compared to oxybutynin; this brings about a significant decrease in side-effects allowing a better treatment compliance in the long term [12][13][14][15][16][17][18][19] . It is available in an immediate-release and in an extended-release formulation.…”
Section: Tolterodinementioning
confidence: 99%
“…Diese sollte man unter Berücksichtigung der Einstellung der Patientin und Indikation anwenden (10) . …”
Section: Hilfsmittelunclassified